Common data items in seven European oesophagogastric cancer surgery registries: Towards a European Upper GI Cancer Audit (EURECCA Upper GI) - REYNOLDS, JOHN (My University, 2014)
Aims Seven countries (Denmark, France, Ireland, the Netherlands, Poland, Sweden, United Kingdom) collaborated to initiate a EURECCA (European Registration of Cancer Care) Upper GI project. The aim of this study was to identify a core dataset of shared items in the different data registries which can be used for future collaboration between countries. Methods Itemlists from all participating Upper GI cancer registries were collected. Items were scored `present? when included in the registry, or when the items could be deducted from other items in the registry. The definition of a common item was that it was present in at least six of the seven participating countries. Results The number of registered items varied between 40 (Poland) and 650 (Ireland). Among the 46 shared items were data on patient characteristics, staging and diagnostics, neo-adjuvant treatment, surgery, postoperative course, pathology, and adjuvant treatment. Information on non-surgical treatment was available in only 4 registries. Conclusions A list of 46 shared items from seven participating Upper GI cancer registries was created, providing a basis for future quality assurance and research in Upper GI cancer treatment on a European level.
PUBLISHED
Keywords: EURECCA; Esophgeal cance